FEATURES OF USING THE MODIFIED METHOD OF PHYSICAL INPUTS IN ESTIMATING THE SCALES OF SHADOW ACTIVITY IN THE RUSSIAN ECONOMY - A. Abroskin; N. Abroskina (Вестник университета)
The issues of improving the methods of measuring the scales of shadow activity in the sectors of the Russian economy have considered. The problem aspects of practical use of the classical method of physical inputs in measuring the scales of shadow activity in the sectors of the national economy have identified. As an alternative to the classical method of physical inputs, its modified version has proposed, based on accounting of the production costs components that dominate in the structure of intermediate consumption. Based on experimental calculations, estimates of the scales of shadow activity in selected sectors of production of goods and services of the Russian economy have developed.